Willingness to pay of multiple stakeholders for non-point source pollution control in a water conservation zone - Du, Yi; Wang, Xiaoyan; Li, Tingting; Li, Kuiming; Nan, Zhe (Frontiers in Environmental Science, 2025)
Stakeholder engagement is crucial for the effective implementation of Diffused Pollution Control Measures (DPCMs), as it fosters local ownership, improves compliance, and enhances the long-term sustainability of environmental initiatives. However, such engagement remains significantly understudied, particularly in developing regions where institutional and resource constraints are prominent. Addressing this gap, this study analyzes the Willingness-To-Pay (WTP) of 221 diverse stakeholders—including volunteers, villagers, and migrants—in rural North China, by examining the interplay of their environmental concern, policy attitudes, and payment intentions to elucidate their motivations and capacity for participation. Results showed that: (1) Stakeholders exhibited four payment archetypes—Institution-Dependent Group, Ambivalent-Concern Group, Responsibility-Cautious Group, Autonomous-Action Group—reflecting motivational disparities in environmental stewardship. (2) Inverse socioeconomic gradients emerged: less-developed Luanping contributed the highest income proportion (0.85%) despite lower absolute payments (68.3 CNY/year), while wealthier Miyun showed higher absolute (69.1 CNY/year) but lower relative contributions (0.36%). Volunteers demonstrated peak absolute WTP (99 CNY/year), surpassing villagers (67.5) and migrants (59.5). (3) Random forest analysis identified WTP (0.318) and income (0.195) as primary determinants (51.3% variance explained), with education, age, and evaluation of government policies as secondary factors. Gender and tendency to seek help showed negligible impacts. These findings underscore that effective payment for DPCMs must integrate economic capacity with trust in policy, while accounting for nuanced stakeholder motivations. The study provides a actionable framework for designing differentiated and socially equitable payment strategies that enhance stakeholder participation and environmental sustainability across diverse socio-economic contexts.